Coeval dry events in the central and eastern Mediterranean basin at 5.2 and 5.6ka recorded in Corchia (Italy) and Soreq caves (Israel) speleothems - Zanchetta, G.; Bar Matthews, M.; Drysdale, R. N.; Ayalon, A.; Hellstrom, J. C.; Isola, I.; Regattieri, E.; LIONELLO, Piero (Global and Planetary Change, 2014)
Soreq (Israel) and Corchia (central Italy) Caves are located 2500km far apart along the Mediterranean winter-storm track and are ideally suited for investigating past variations of winter rainfall in the Mediterranean region. Analyses of speleothem δ18O records from both caves for the period between ca. 7 to 4 ka BP show some striking similarities for the ca. 6 and 4ka interval, but lack agreement between ca. 7 to 6kaBP. Two prominent isotopic excursions, argued to reflect relatively drier conditions, are centred at ca. 5.6 and ca. 5.2 ka. The 5.2 ka event lasts less than a century, whereas the 5.6ka event extends from ca. 5.7 to 5.4 ka. A period of progressive drying is also apparent from ca. 5 to 4ka. Another prominent event, reflecting wetter conditions, is recorded in both records at ca. 5.8ka and seems to last several decades. The 5.6 and 5.2ka events occurred within a period of higher deposition of haematite-stained grains in cores of the sub-polar North Atlantic, and correlation with the wind strength proxy record from Hólmsá loess profile in Iceland suggests that rainfall reduction was related to a reduced vapour advection from Atlantic towards the Mediterranean connected to northward shift in the Westerlies. A comparison with Alpine records, including the Spannagel Cave isotope record, suggests that dry events recorded at Soreq and Corchia caves may correspond to wetter (lake high stands) and cooler (glacier expansion) conditions in the Alpine region, indicating complex regional climate re-organization